Mitochondria and plasma membrane Ca2+‐ATPase control presynaptic Ca2+ clearance in capsaicin‐sensitive rat sensory neurons. (1st March 2013) - Shutov, Leonid P.; Kim, Man‐Su; Houlihan, Patrick R.; Medvedeva, Yuliya V.; Usachev, Yuriy M.
Key points The first sensory synapse formed between the central processes of primary afferents and dorsal horn neurons plays an important role in controlling the flow of nociceptive information from the periphery to the CNS, and plasticity at this synapse contributes to centrally mediated pain hypersensitivity. Although exocytosis and synaptic plasticity are regulated by presynaptic Ca2+, the mechanisms underlying presynaptic Ca2+ signalling at the first sensory synapse are not well understood. In this study we show that the plasma membrane Ca2+‐ATPase and mitochondria are the major regulators of presynaptic Ca2+ signalling in capsaicin‐sensitive dorsal root ganglion neurons accounting for ∼47 and ∼40% of presynaptic Ca2+ clearance, respectively. Quantitative analysis of changes in cytosolic and mitochondrial Ca2+ concentrations demonstrates that the mitochondrial Ca2+ uniporter is highly sensitive to cytosolic Ca2+ at this synapse. These results help us understand presynaptic mechanisms at the first sensory synapse. Abstract The central processes of primary nociceptors form synaptic connections with the second‐order nociceptive neurons located in the dorsal horn of the spinal cord. These synapses gate the flow of nociceptive information from the periphery to the CNS, and plasticity at these synapses contributes to centrally mediated hyperalgesia and allodynia. Although exocytosis and synaptic plasticity are controlled by Ca2+ at the release sites, the mechanisms underlying presynaptic Ca2+ signalling at the nociceptive synapses are not well characterized. We examined the presynaptic mechanisms regulating Ca2+ clearance following electrical stimulation in capsaicin‐sensitive nociceptors using a dorsal root ganglion (DRG)/spinal cord neuron co‐culture system. Cytosolic Ca2+ concentration ([Ca2+]i) recovery following electrical stimulation was well approximated by a monoexponential function with a τ∼2 s. Inhibition of sarco‐endoplasmic reticulum Ca2+‐ATPase did not affect presynaptic [Ca2+]i recovery, and blocking plasmalemmal Na+/Ca2+ exchange produced only a small reduction in the rate of [Ca2+]i recovery (∼12%) that was independent of intracellular K+. However, [Ca2+]i recovery in presynaptic boutons strongly depended on the plasma membrane Ca2+‐ATPase (PMCA) and mitochondria that accounted for ∼47 and 40%, respectively, of presynaptic Ca2+ clearance. Measurements using a mitochondria‐targeted Ca2+ indicator, mtPericam, demonstrated that presynaptic mitochondria accumulated Ca2+ in response to electrical stimulation. Quantitative analysis revealed that the mitochondrial Ca2+ uptake is highly sensitive to presynaptic [Ca2+]i elevations, and occurs at [Ca2+]i levels as low as ∼200–300 nm. Using RT‐PCR, we detected expression of several putative mitochondrial Ca2+ transporters in DRG, such as MCU, Letm1 and NCLX. Collectively, this work identifies PMCA and mitochondria as the major regulators of presynaptic Ca2+ signalling at the first sensory synapse, and underlines the high sensitivity of the mitochondrial Ca2+ uniporter in neurons to cytosolic Ca2+.